GREATER TROCHANTERIC PAIN SYNDROME: DEFINING THE SYNDROME. Issue 9 (10th May 2013) - Fearon, A M; Scarvell, J M; Cook, J L; Neeman, T; Cormick, W; Smith, P N
Abstract : Introduction: Effective treatment of hip pain leads to improved quality of life and population health. This is dependent on accurate differential diagnosis. While hip osteoarthritis (OA) diagnosis is well defined, 1 the diagnosis of greater trochanteric pain syndrome (GTPS) is not. The aim of this study was to clinically define GTPS. Methods: Forty one people with GTPS, ranging from mild to severe (11 not seeking treatment and 10 awaiting surgery), 20 with severe hip OA, and 23 age and sex matched asymptomatic participants (ASC) were recruited from public and private hospitals, and the community. Inclusion and exclusion criteria assured mutually exclusive groups. Assessment included the Harris Hip Score (HHS), a battery of passive and resisted tests (recording reproduction and location of pain), and the single leg stance test. Statistical analyses used include Fisher exact test, ANOVA, and recursive partitioning to develop two classification trees. The first classification tree was based on an undifferentiated hip pain response and the second was based on a clearly identified lateral hip pain response. Results: The HHS domains of maximum walking distance and the ability to manipulate shoes and socks were the only domains to differentiate between the two symptomatic groups, (ANOVA: p=0.010 and p<0.001 respectively). Dichotomising these data resulted in OR (95% CI) of 3.47 (1.09 to 10.93)—for the ability to walk >30/60; and of 0.06 (0.00 to 0.26)—for the ability to manipulate shoes and socks, of having GTPS versus hip OA. The first classification tree resulted in a four branch tree for diagnosing GTPS, with a mean (se) sensitivity and specificity of 0.78 (0.058) and 0.28 (0.080) respectively. These branches included a positive Ober and passive to active medial rotation ratios. The second tree resulted in one branch, FABER, for diagnosing GTPS with a mean (se) sensitivity and specificity of 0.81 (0.019) and 0.82 (0.044) respectively. The single leg stance test did not differentiate between the two symptomatic groups. Discussion: Three features differentiated people with GTPS from those with hip OA without reference to our inclusion criteria. These results provide clinicians with markers to aid with the sometimes difficult diagnosis of GTPS.2 When combined with greater trochanter palpation, this combination of features is likely to be more sensitive and specific than the FABER test result. We recommend that the clinical syndrome of GTPS be defined as a history of lateral hip pain in the absence of difficulty with manipulating shoes and socks, together with an examination of findings of pain reproduction on palpation of the greater trochanter (a previously recognised sign) and lateral hip pain with a FABER test. In patients who cannot differentiate the site of their pain, multiple pathologies should be considered. For research purposes or in cases of poor response to treatment, multiple pathologies should be considered and a hip x-ray should be undertaken to exclude joint pathology.